Analisis Hubungan Waktu Tunggu Pelayanan Obat, Kinerja Pelayanan Kesehatan, Kualitas Informasi Kesehatan dan Tingkat Kepuasan Pasien: Analysis of the Relationship Between Drug Service Waiting Time, Health Service Performance, Health Information Quality, and Patient Satisfaction Level - Fenia, Dinda; Roslan, Rosidi; Saputra, Fajar (MPI Press, 2024)
Introduction: In this modern era, healthcare services have become a primary focus for society. Patients require efficient and quality services to meet their health needs. This study aims to analyze the relationship between medication service waiting time, health service performance, health information quality, and patient satisfaction levels at UPTD Puskesmas X in Depok City. Objectives: This study aims to analyze the relationship between medication service waiting time, health service performance, health information quality, and patient satisfaction levels at UPTD Puskesmas X in Depok City in 2024. Method: This type of research is quantitative with a purposive sampling design, involving a sample of 171 patient respondents. The instruments in this study use data collection techniques through questionnaires. Data analysis is conducted univariately and bivariately using the chi-square test. Result: Based on the research results, there is a significant relationship between medication service waiting time and patient satisfaction, as indicated by the chi-square test (p=0.000<0.05) with an Odds Ratio (OR) of 5.884. There is also a significant relationship between health service performance and patient satisfaction, with a chi-square test result of (p=0.002<0.05) and an OR of 2.667. Additionally, a significant relationship exists between health information quality and patient satisfaction, with a chi-square test result of (p=0.002<0.05) and an OR of 2.661. Conclution: That there is a relationship between medication service waiting time, health service performance, health information quality, and patient satisfaction levels at UPTD Puskesmas X in Depok City in 2024.